P-024 Scepter C™ Balloon Occlusion Device use for Liquid Embolisation of Vascular Malformations, a Pilot Study. (14th July 2013) - Grupke, S; Alhajeri, A; Fraser, J
Abstract : Objective: The Scepter C™ balloon occlusion catheter (Microvention, Tustin CA) is an endovascular device designed with a polyurethane balloon that elongates with inflation to allow it to conform to the lumen of the target vessel. The device has a double lumen, allowing passage over a 0.014-inch guidewire, and/or passage of Onyx embolisation distal to the balloon. We reviewed our initial use of this device as a conduit for liquid embolisation of vascular malformations as compared to the Marathon™ microcatheter (ev3, Plymouth, MN) alone, outlining indications for and outcomes with use. Methods: We performed a retrospective review of patients who underwent Onyx embolisation of an arterovenous malformation or a dural A-V fistula from October 2011 to February 2013 at the University of Kentucky Hospital. Results: 14 Scepter C™ devices were used in 8 patients over the course of 10 endovascular interventions. We compared this to 8 patients treated with 11 embolisations over the course of 9 interventions without balloon assistance. Technical success was achieved in 13/14 (93%) deployments of the balloon. There were no complications related to Scepter C™ use. Scepter C™ permitted distal navigation, while facilitating faster Onyx injection with more extensive and distal casting. This led to a trend of decreased fluoro time per embolisation with Scepter C™, though not statistically significant (23.0 ± 8.8 min vs 34.0 ± 10.4 min). There were no cases of Onyx fixation of the device in the parent artery; no significant tension was required to remove the device after Onyx injection. This represents a significantly different experience from the typically used Onyx microcatheter (Marathon), which carries a known risk of tip-adhesion to the Onyx cast. We detail technical nuances used to maximise the benefits of the Scepter C™ for such applications. Conclusions: The Scepter C balloon catheter has, thus far, proven to be a safe and effective device for the endovascular treatment of vascular malformations through Onyx embolisation. A larger prospective study should be undertaken to ascertain any potential advantages or disadvantages compared to the current standard delivery catheters. Disclosures: S. Grupke: None. A. Alhajeri: None. J. Fraser: None.